Handle force measurements with the BioRowTech erg system - Kleshnev, V. (BioRow, 2018)
A new addition to the BioRowTech system for the rowing ergometer has recently been developed. Handle force can now be measured using the BioRowTech system in addition to the velocities of the three main body segments.